Influence of gene mutations on inflammation, oxidative stress and endothelial function in patients with familial hypercholesterolaemia / Prof. Dr. Hapizah Mohd Nawawi … [et al.] - Mohd Nawawi, Hapizah; Tengku Ismail, Tengku Saifudin; Abdul Rahman, Thuhairah Hasrah; Krishnapilla, Ambigga Devi; Ramli, Anis Safura (Research Management Institute (RMI), 2010)
Background: Familial hypercholesterolaemia (FH) is a monogenic co-dominant disorder characterized by elevated plasma low-density lipoprotein cholesterol (LDL-C) levels and increased risk of premature coronary artery disease (CAD). Objective: To compare the oxidative stress and inflammatory status between FH patients and normocholesterolaemic (NC) subjects…